Proposed establishment of a church library in Sto. Cristo Parish, Las Piñas City - Rondero, Charmine Ann G. (School of Library and Information Studies, University of the Philippines Diliman, 2010)
The history of libraries include church libraries. However, the use of church libraries was limited only for the scholars, clergy and the Church authority. Today, church libraries are also available for the public. Unfortunately, this is not yet known in the Philippines especially in the Roman Catholic Church. This is the reason why this study focused on the feasibility of establishing a church library in Sto. Cristo Parish.